Association of PM2.5 With blood lipids and dyslipidaemia in a rural population of north-western china - Wang, Kairong; Zhao, Yi; Wang, Qingan; Zhang, Yajuan; Zhang, Yuhong (Frontiers in Environmental Science, 2022)
Background: Evidence regarding the association between particulate matter with aerodynamic diameter ≤2.5 μm (PM2.5) and blood lipid levels is insufficient in the rural areas of developing countries. Few studies have estimated the role of PM2.5 in blood lipid levels. We investigated the relationship between long-term exposure to PM2.5, blood lipids, and dyslipidaemia in rural Chinese adults. Methods: Baseline data of 15,802 participants (aged 35–74 years) in the China Northwest Cohort-Ningxia Project were used in this study. PM2.5 levels were assessed using satellite remote sensing data in accordance with each participant’s home address. Personally exposed PM2.5 was defined as the 3-year mean concentration prior to the baseline survey. Logistic and linear models were utilised to quantify the associations of PM2.5 with the prevalence of dyslipidaemia and with blood lipids, including total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Results: The 3-year mean level of PM2.5 was 35.36 ± 4.21 μg/m3. Every 1-μg/m3 increase in PM2.5 was related to an increase of 0.04% (95% CI: −0.44–0.53%) in TG and decreases of 0.37% (95% CI: 0.16–0.90%) in TC, 5.76% (95% CI: 5.32–6.21%) in LDL-C, and 0.89% (95% CI: 0.72–1.05%) in HDL-C. Every 1-μg/m3 increment in PM2.5 was related with a 4% (95% CI:3–5%) and 18% (95% CI:16–20%) higher risk of dyslipidaemia and hypoalphalipoproteinemia, respectively, and a decrease of 11% (95% CI:10–13%) in hyperbetalipoproteinemia. Sex, age, and BMI were adjusted for the relationships between PM2.5, blood lipids, and dyslipidaemia. Conclusion: Greater PM2.5 exposure was related to harmful changes in blood lipids and dyslipidaemia. Male, elderly, and overweight individuals may be more vulnerable to the negative effects of PM2.5.